2011
DOI: 10.1111/j.1754-8845.2011.01095.x
|View full text |Cite
|
Sign up to set email alerts
|

Now you see me, now you don’t: From reader to student and back again in A‐Level English Literature

Abstract: In this paper I investigate students' experience of the assessment regime in A-Level English literature, and present data from a small-scale interview study with students intending to study English at university. Research has shown that students experience conflict between reading for pleasure and reading for assessment; and I draw upon Bernstein's work on invisible and visible pedagogies to explain how the personal response hinders interpretation of text they do not find pleasurable. Interview data explore so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In this article we explore, from a cognitive linguistic perspective, the ways by which English teaching can support students in turning their interpretations into rich, critical but also authentic readings. Research has shown that teachers and students are very much aware of the impact studying can have on ‘reading for pleasure’ (Nash ; Nightingale ). They describe this difference in a variety of ways, but it generally manifests in a sense of ‘something getting lost’ in the context of overpowering assessment and accountability regimes (Maybin ; Turvey and Lloyd ).…”
Section: Reading and Authenticitymentioning
confidence: 99%
“…In this article we explore, from a cognitive linguistic perspective, the ways by which English teaching can support students in turning their interpretations into rich, critical but also authentic readings. Research has shown that teachers and students are very much aware of the impact studying can have on ‘reading for pleasure’ (Nash ; Nightingale ). They describe this difference in a variety of ways, but it generally manifests in a sense of ‘something getting lost’ in the context of overpowering assessment and accountability regimes (Maybin ; Turvey and Lloyd ).…”
Section: Reading and Authenticitymentioning
confidence: 99%